Evan Olea: capstone - Olea, Evan, artist (Colorado State University. Libraries, 2019)
The artist's statement: As an artist and graphic designer I focus strongly on purposeful work and clean design that is both impactful and successful in its intended purpose. My design work is impacted by some major personal traits, which include dedication to detail and focus on consistent communication, whether that is through emphasizing a brands voice or maintaining a singular ads purpose through its design. This forethought is placed into another important step in beginning a design project - context and how the design concept can best be applied and adapted to all possible parts of a project in digital, print, or both. I am also a curator and creator in the development of my work. Being up to date on both design trends but also referencing traditional art concepts on how we perceive information visually, is at the forefront of my process when beginning a project. Utilizing UI (User Interface) and UX (User Experience) design laws, are an important step I take with a majority of projects and can be applied to nearly every kind of design, even in illustration. Daily practice with design as my profession, is an opportunity that comes from hard work and its a position I truly value, especially when working with clients. I truly value my profession as it allows me to pursue and combine the strong passions I have for creation, communication, coordination, and research. I graduated with a Bachelor's Degree in Graphic Design from Colorado State University in 2019. That experience brought many valuable lessons in design into my daily practice. This led to an opportunity to work for the University as a junior designer then supervising designer for the last two years, which focused on large-scale, multi-part projects, company branding, and event advertising.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design